A case of leptospirosis reported from metropolitan city of central India - Dhruvendra Pandey; Satish Saroshe; Sanjay Dixit; Chakresh Jain (Wolters Kluwer Medknow Publications, 2015)
Leptospirosis is an emerging public health problem in India which affects both human and animals. A 62 years old male, resident of rural area presented in out patient department of a private super specialty hospital with complaints of fever with chills, pain in abdomen and difficulty in breathing. His initial investigation showed plasmodium vivax positive, acute cholecystitis, elevated liver enzyme and thrombocytopenia. He was unresponsive for intravenous antibiotics. Next day he developed per rectal bleeding. After negative finding of dengue testing, diagnostic test for leptospirosis was applied, which was positive. This case of leptospirosis should serve to alert health-care providers and the general public regarding the clinical and public health importance of this severe, sometimes fatal, disease.